ANALISIS REAKSI PASAR MODAL ATAS PERISTIWA PEMILIHAN PRESIDEN 9 JULI 2014 (EVENT STUDY PADA INDEKS SAHAM LQ-45) - Dewi Arum Melati; Saryadi Saryadi; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2015)
Presidential election in Indonesia considered as a big event which held in every 5 years. Presidential Election July 9 2014 is one of the important event in Indonesia and the capital market shows that there are some reactions of the event. This research aims to see how the reaction of capital market by looking at the differences of each three variabel in this research, they are bid ask spread, abnormal return, and trading volume activity before and after presidential election, July 9 2014. The research object is 45 companies which listed in LQ-45 Index period during February – July 2014. The observation period is 24 days which is 12 days before and after presidential election event at July 9 2014. This hypothesis test used paired sample t-test analysis. The result of this research shows that there is no significant differences beetween bid ask spread before and after presidential election, there is no significant differences beetween abnormal return before and after presidential election, and there is a significant differences beetween trading volume activity before and after presidential election.